2015
DOI: 10.1186/s13287-015-0256-1
|View full text |Cite
|
Sign up to set email alerts
|

Combining mesenchymal stem cell sheets with platelet-rich plasma gel/calcium phosphate particles: a novel strategy to promote bone regeneration

Abstract: BackgroundPromotion of bone regeneration is important for successful repair of bony defects. This study aimed to investigate whether combining bone marrow-derived mesenchymal stem cell (BMSC) sheets with platelet-rich plasma (PRP) gel/calcium phosphate particles could promote bone formation in the femoral bone defects of rats.MethodsThe proliferation and differentiation of BMSCs or BMSC sheets cultured with calcium phosphate particles and/or PRP were investigated in in vitro. In vivo, 36 2.5 × 5 mm bone defect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
44
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…Qi et al (38) also found that stem cell sheet transplantation promoted bone formation in a rat tibia osteotomy model. Meanwhile, the BMSC sheet exhibited a marked positive effect on bone regeneration in a rat femoral osteotomy model (43).…”
Section: Discussionmentioning
confidence: 99%
“…Qi et al (38) also found that stem cell sheet transplantation promoted bone formation in a rat tibia osteotomy model. Meanwhile, the BMSC sheet exhibited a marked positive effect on bone regeneration in a rat femoral osteotomy model (43).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the concentrated growth factors in PRP increase revascularization, promote mesenchymal stem cell and osteoblast development into osteocytes, and encourage granulation tissue formation to fill the defect. 107,108 PRP treatment for osteomyelitis in preclinical animal models A rabbit model of MRSA tibial bone infection has been used to determine the efficacy of L-PRP gel implanted into the infected bone. Six weeks after debridement, antibacterial efficacy and new bone formation were measured.…”
Section: Possible Mechanisms Of Prp Treatment For Osteomyelitismentioning
confidence: 99%
“…Recent animal data confirm that the combination of MSCs with platelet-rich plasma most efficiently promoted bone regeneration in the presence of high calcium levels [30]. In addition to these direct, pro-regenerative and tissue reconstructive approaches, immunomodulatory intervention strategies have been reported to maximize regenerative and minimize destructive effects of inflammation leading to enhanced bone fracture healing in animal experiments [31,32,33].…”
Section: Introductionmentioning
confidence: 99%